IbM MIE SEHAT - Sunardi Sunardi; Soebiyanto Soebiyanto; Maria Endah Prasadja (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
The purpose of this activity are: 1) improve the quality and productivity of UKM through the provision of machine presses for first partners and machine dough mixer for second partners; 2) help create tranquility, security and comfort in consuming wet noodle through noodle products that meet the quality requirements SNI 01-2987-1992; 3) improve financial management and marketing to both partners. Specific target availability noodle products are hygienic and healthy appropriate quality requirements SNI 01-2987-1992.Kata kunci : Wet noodle, hygienic, healty